“If Sweden is a province, what are we?” Map-making and man-making in Marius Ivaškevičius’s essay series My Scandinavia - Körber, Lill-Ann; Steponavičiūtė-Aleksiejūnienė, Ieva (Folia Scandinavica Posnaniensia, 2023)
This co-written article approaches the influential Lithuanian writer and playwright Marius Ivaškevičius’s essay series My Scandinavia (2004) from two different vantage points reflecting either side of the former ‘Iron Curtain’. Published in the year when Lithuania joined the European Union, the essay series describes the narrator’s travels and symbolic and ironic conquest of Northern Europe in the wake of the border openings following the collapse of the Soviet Union. First, employing the notions of “temporal” and “spatial nodes” (Ringgard & DuBois 2017), the article addresses how the crossings of the Baltic Sea and journeys through Northern Europe depicted in Ivaškevičius’s essays represent an awareness of significant shifts in the unfolding of European history and Europe’s spatial configuration. Second, the article reads My Scandinavia as an example of creative map-making in line with theories of critical cartography. Finally, the article puts the travelling subject in My Scandinavia centre stage, looking at the dialectic ways in which subject and place create each other. Just as Scandinavia has been actively moulding the narrating and, by implication, also the writing subject’s biography, so has he given Scandinavia shape through his discourse, while also idiosyncratically framing Europe’s shifting political and mental geography.